2019
DOI: 10.1186/s12891-019-2866-8
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell tumor of tendon sheath in the hand: analysis of risk factors for recurrence in 50 cases

Abstract: Background: Giant cell tumor of the tendon sheath is the most common form of giant cell tumors and is the second most common soft tissue tumor of the hand region after ganglion cyst. Magnetic resonance imaging is the diagnostic tool of choice for both diagnosis and treatment planning. The current standard treatment of choice is simple excision. The main concern about the treatment is related to the high recurrence rates. Besides incomplete excision, there is no consensus concerning the effect of other risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
81
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(87 citation statements)
references
References 23 publications
3
81
0
3
Order By: Relevance
“…This rate is similar to the literature. [12,13] We had recurrence in a 13-year-old female patient. The GCTTS was multilobulated and multifocal in that patient and we think that the reason for recurrence was the inadequate resection.…”
Section: Discussionmentioning
confidence: 95%
“…This rate is similar to the literature. [12,13] We had recurrence in a 13-year-old female patient. The GCTTS was multilobulated and multifocal in that patient and we think that the reason for recurrence was the inadequate resection.…”
Section: Discussionmentioning
confidence: 95%
“…Williams et al reported the overall recurrence rates ranged from 7 to 44% [ 10 ]. Hakan recorded the recurrences were 6% [ 11 ]. At present, radical surgical management is particularly important to reduce recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Some authorities declare it to be an inflammatory disease whereas others consider it to be a neoplastic entity. [1][2][3] At the time of radical surgical excision, the surgeon is often faced with unique challenges. Being originating from the synovial sheaths, one has to be careful to dissect the entire tumor and at the same time, preserve the underlying tendons.…”
mentioning
confidence: 99%
“…Rarely, these have to be sacrificed to ensure complete excision. [1][2][3][4][5] The low recurrence rate in this study is attributable to the routine employment of preoperative workup with MRI and FNAC, use of intraoperative loupe magnification, and meticulous surgical technique that ensured radical resection without missing any satellite lesions.…”
mentioning
confidence: 99%